Potent Inhibition of HIV-1 Reverse Transcriptase and Replication by Nonpseudoknot, “UCAA-motif” RNA Aptamers - Whatley, Angela S (Nature Publishing Group, 2013)
RNA aptamers that bind the reverse transcriptase (RT) of human immunodeficiency virus (HIV) compete with nucleic acid primer/template for access to RT, inhibit RT enzymatic activity in vitro, and suppress viral replication when expressed in human cells. Numerous pseudoknot aptamers have been identified by sequence analysis, but relatively few have been confirmed experimentally. In this work, a screen of nearly 100 full-length and >60 truncated aptamer transcripts established the predictive value of the F1Pk and F2Pk pseudoknot signature motifs. The screen also identified a new, nonpseudoknot motif with a conserved unpaired UCAA element. High-throughput sequence (HTS) analysis identified 181 clusters capable of forming this novel element. Comparative sequence analysis, enzymatic probing and RT inhibition by aptamer variants established the essential requirements of the motif, which include two conserved base pairs (AC/GU) on the 5′ side of the unpaired UCAA. Aptamers in this family inhibit RT in primer extension assays with IC(50) values in the low nmol/l range, and they suppress viral replication with a potency that is comparable with that of previously studied aptamers. All three known anti-RT aptamer families (pseudoknots, the UCAA element, and the recently described “(6/5)AL” motif) are therefore suitable for developing aptamer-based antiviral gene therapies.